The role of inflammasome in chronic viral hepatitis - Wan, Pin; Yang, Ge; Cheng, Qi; Zhang, Xuelong; Yue, Zhaoyang; Li, Moran; Liu, Chunlin; Yi, Qian; Jia, Yaling; Liu, Jinbiao; Xing, Xiwen; Sun, Binlian; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Infections of hepatotropic viruses cause a wide array of liver diseases including acute hepatitis, chronic hepatitis and the consequently developed cirrhosis and hepatocellular carcinoma (HCC). Among the five classical hepatotropic viruses, hepatitis B virus (HBV) and hepatitis C virus (HCV) usually infect human persistently and cause chronic hepatitis, leading to major troubles to humanity. Previous studies have revealed that several types of inflammasomes are involved in the infections of HBV and HCV. Here, we summarize the current knowledge about their roles in hepatitis B and C. NLRP3 inflammasome can be activated and regulated by HBV and HCV. It is found to exert antiviral function or mediates inflammatory response in viral infections depending on different experimental models. Besides NLRP3 inflammasome, IFI16 and AIM2 inflammasomes participate in the pathological process of hepatitis B, and NALP3 inflammasome may sense HCV infection in hepatocytes. The inflammasomes affect the pathological process of viral hepatitis through its downstream secretion of inflammatory cytokines interleukin-1β (IL-1β) and IL-18 or induction of pyroptosis resulting from cleaved gasdermin D (GSDMD). However, the roles of inflammasomes in different stages of viral infection remains mainly unclear. More proper experimental models of viral hepatitis should be developed for specific studies in future, so that we can understand more about the complexity of inflammasome regulation and multifunction of inflammasomes and their downstream effectors during HBV and HCV infections.